The Relationship Between Self-Talk and Emotion Regulation in Volleyball Athletes in Kabupaten Bandung Barat - Amelia Musyarofah; Muhamad Tafaqur; Ridha Mustaqim (Universitas Negeri Semarang, 2025)
To achieve optimal performance in training and competition, internal dialogue and emotional regulation are two important aspects that need to be considered. Research on the relationship between self-talk and emotional regulation shows that self-talk plays a role in improving emotional control, reducing anxiety, and helping athletes maintain focus when facing competitive pressure. Specifically in volleyball, athletes often find it difficult to regulate their emotions and self-talk, which prevents them from performing at their best. This study aims to determine the relationship between self-talk and emotional regulation in volleyball athletes in West Bandung Regency. A quantitative descriptive method with a correlational design was used in this study. Twenty-four volleyball athletes from West Bandung Regency participated in this study as samples. A questionnaire to measure self-talk and emotional regulation was given to the samples once. After that, the data were processed and analyzed using SPSS Version 25. The results showed that there was a significant relationship between self-talk and emotional regulation among volleyball athletes. This study concluded that self-talk plays an important role in regulating the emotions of volleyball athletes in West Bandung Regency to achieve their desired goals, namely performance.